1989
DOI: 10.1007/bf00762728
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen diffusion-concentration in erythrocyte plasma membranes studied by the fluorescence quenching of anionic and cationic pyrene derivatives

Abstract: Fluorescence quenching by oxygen of cationic [pyrene-(CH2)nN(CH3)3+; n = 1, 4, and 11] and anionic [pyrene-(CH2)nCO2-, n = 3, 8, 11, and 15] probes was investigated in erythrocyte plasma membranes (leaky) in order to assess the ability of oxygen molecules to interact with solutes located at different positions in the membrane. The pseudounimolecular quenching rate constants measured increase, both for cationic and anionic probes, when n increases. These results are interpreted in terms of an increased oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…This value accounts for the entire bilayer, including polar phosphocholine headgroups. However, there is evidence indicating that O 2 , ⅐ NO, and other apolar molecules, are less favorably dissolved in this region of the membrane (33)(34)(35)40) and should therefore be excluded from the hydrophobic volume. We assumed a 0.75 bilayer hydrophobic fraction, thus the corrected K P from Smotkin et al (37) would be 4.9 Ϯ 0.8, which is in agreement within experimental errors with that found by ourselves (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…This value accounts for the entire bilayer, including polar phosphocholine headgroups. However, there is evidence indicating that O 2 , ⅐ NO, and other apolar molecules, are less favorably dissolved in this region of the membrane (33)(34)(35)40) and should therefore be excluded from the hydrophobic volume. We assumed a 0.75 bilayer hydrophobic fraction, thus the corrected K P from Smotkin et al (37) would be 4.9 Ϯ 0.8, which is in agreement within experimental errors with that found by ourselves (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…It is nowadays used for membrane fluidity detection [3] and oxygen sensing film [4]. Other pyrene derivatives allow measurement of oxygen concentrations in living cells by the detection of fluorescence intensity variations [5,6] or fluorescence lifetime changes [7]. Lifetime measurements are not dependent on the absolute intensity of the emitted light and, therefore, independent of the probe concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Because acclimation‐induced increase in fatty acid desaturation (Fig. 3) leads to membrane fluidization (Thompson 1979), and an accompanying stimulation in cross‐membrane gas permeability (Zander 1976, Lissi and Caceres 1989), we examined whether acclimation may also enhance respiratory gas exchange. The results revealed that in acclimated cucumber seedlings (48 h at 12°C) there was a respiratory upsurge during the follow‐up warming period (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-membrane permeability constrains oxygen diffusion to the cellular interior (Grinberg et al 1998) and this process is restrained further by chilling-induced membrane-lipid rigidification (Dumas et al 1997). Because acclimation-induced lipid re-tailoring leads to membrane-lipid fluidization (Thompson 1979(Thompson , 1983 and because membranelipid fluidity enhances gas permeability (Zander 1976, Lissi andCaceres 1989), we reasoned that cold acclimation might also lead to enhanced respiratory gas exchange in cucumber seedlings. The results show, accordingly, a higher respiratory gas exchange in acclimated compared with non-acclimated cucumber seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation